2001
DOI: 10.1007/s001010050998
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoskopische Intubation in Remifentanil-Propofol-Sedierung

Abstract: Our combination of remifentanil and propofol was shown to be a safe sedation regimen for fiberoptic intubation. Monitoring ventilation via nasal capnography and arterial oxygen saturation via pulse oximetry provided sufficient patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…No patient became hypoxic, and the heart rate and blood pressure remained within 30% of baseline in all but one. 9 A greater body of published work has focused on targetcontrolled infusion (TCI) of propofol for AFOI, either as the sole agent or in combination with remifentanil. [10][11][12][13] Targetcontrolled infusions of propofol for AFOI have been assessed in three RCTs providing level 1 evidence comparing it with remifentanil (Table 2) 10-12 and in one RCT comparing it with dexmedetomidine.…”
Section: Principles Of Safe Sedation For Afoimentioning
confidence: 99%
See 1 more Smart Citation
“…No patient became hypoxic, and the heart rate and blood pressure remained within 30% of baseline in all but one. 9 A greater body of published work has focused on targetcontrolled infusion (TCI) of propofol for AFOI, either as the sole agent or in combination with remifentanil. [10][11][12][13] Targetcontrolled infusions of propofol for AFOI have been assessed in three RCTs providing level 1 evidence comparing it with remifentanil (Table 2) 10-12 and in one RCT comparing it with dexmedetomidine.…”
Section: Principles Of Safe Sedation For Afoimentioning
confidence: 99%
“…9,10,[14][15][16] More recently, case reports have described the concurrent use of propofol TCI with remifentanil TCI for AFOI [14][15][16] Authors describing the combined use of TCI propofol and remifentanil for AFOI have reported mean effect-site concentrations during the procedure of 0.8-2.0 lgÁmL -1 and 1.5-3.2 ngÁmL -1 , respectively. Although there is no evidence supporting the superiority of TCI propofol over a fixed rate infusion in the setting of an AFOI, it is safe to say that a TCI has a more consistent pharmacodynamic effect and may allow for a more predictable level of sedation to be maintained.…”
Section: -13mentioning
confidence: 99%
“…Remifentanil has previously been used as a sole agent and also in combination with propofol and midazolam for sedation for awake fibreoptic intubation [2,3,[5][6][7]. Neidhardt and colleagues studied 40 patients sedated with propofol 2 mg.kg )1 .h )1 and remifentanil commenced at 0.05 lg.kg )1 .min )1 and adjusted thereafter according to respiratory rate [5].…”
Section: Discussionmentioning
confidence: 99%
“…Neidhardt and colleagues studied 40 patients sedated with propofol 2 mg.kg )1 .h )1 and remifentanil commenced at 0.05 lg.kg )1 .min )1 and adjusted thereafter according to respiratory rate [5]. Intubation was successful in all patients and oxygen saturation remained above 93%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation